2017
DOI: 10.1159/000458730
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Seizures and Epilepsy after Decompressive Hemicraniectomy for Malignant Middle Cerebral Artery Stroke

Abstract: Background: Decompressive hemicraniectomy (DHC) is a life-saving procedure for treatment of large malignant middle cerebral artery (MCA) strokes. Post-stroke epilepsy is an additional burden for these patients, but its incidence and the risk factors for its development have been poorly investigated. Objective: To report the prevalence and risk factors for post-stroke seizures and post-stroke epilepsy after DHC for treatment of large malignant MCA strokes in a cohort of 36 patients. Methods: In a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
5
21
0
Order By: Relevance
“…This is relevant when determining when and how long to maintain ASD therapy. Studies have previously shown that cortical infarcts particularly in the middle cerebral artery territory influence the risk of PSS recurrence [31,32]. This agrees with our results demonstrating a higher incidence of anterior circulation infarcts in patients with PSS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is relevant when determining when and how long to maintain ASD therapy. Studies have previously shown that cortical infarcts particularly in the middle cerebral artery territory influence the risk of PSS recurrence [31,32]. This agrees with our results demonstrating a higher incidence of anterior circulation infarcts in patients with PSS.…”
Section: Discussionsupporting
confidence: 93%
“…A subset of ischemic stroke patients who underwent decompressive hemicraniectomy for large middle cerebral infarctions was assessed. Over 1086 days, seizures occurred in 22 of 36 patients (61.1%), demonstrating a very high incidence of PSS in this population [31]. In our study, a small number of patients were operated on and no difference was found between those with and without PSS.…”
Section: Discussionmentioning
confidence: 43%
“…In the DECIMAL trial (DEcompressive Craniectomy In MALignant MCA Stroke), authors observed greater risk of seizures in patients with malignant middle cerebral artery stroke, independently of decompressive craniectomy, being 6 of 15 survivors (40%) with craniectomy and 2 of 4 survivors (50%) without decompressive hemicraniectomy (81). We have previously observed similar rates after decompressive craniectomy (82). Our data showed that initial NIHSS scores correlate with seizures or epilepsy development.…”
Section: Discussionsupporting
confidence: 63%
“…In another study, Brondani et al reported the prevalence of seizures in 61% (21 out of 36) of the patients with malignant MCA infarction undergoing DC. Furthermore, 59% (19 out of 34) patients developed epilepsy ( 33 ). Although a non-significant difference existed between TBI patients with or without seizures (incidence of 10.8%), the hospital stay prolonged significantly in the former group ( 35 ).…”
Section: Early Complicationsmentioning
confidence: 99%